The role of gladiators in the criminal plot of the Ides of March 44 BC according Nicholas of Damascus Βίος Καίσαρος - Perea Yébenes, Sabino (Gerión. Revista de Historia Antigua, 2013)
Taking as starting point the work of Nicolaus of Damascus entitled Βίος Καίσαρος, which relates the last moments in the life of Julius Caesar and the first years in Octavianus’ political career, my intention here is to collect and examine the news given by this roman author (who wrote in the time of Augustus) about the role played by the gladiators during the Ides of March in the year 44 BC. These gladiators, who had been recruited by the conjurers, served to protect the rearguard of the pro-coup side and also as an armed escort of the rebel leaders during their march towards the Capitol and the Forum. Finally, gladiators and slaves were the “first political clientele” of the murderers, so they reflect the scarce social support that conspirators found in the city of Rome.